Development of Spinning Wheel-Based Question Thread Pull Media on Atomic Structure Material to Train Student Communication Skills - Khasanah, Adellia Nur; Rusmini, Rusmini (Jurnal Pijar Mipa, 2025)
Atomic structure material is important to learn and understand because it is the basis of chemistry learning, but in reality, it is still found that students' academic abilities are lacking in this material. In addition, students' communication skills are still relatively poor in the learning process. Therefore, innovative learning media is needed that can improve students' academic ability in atomic structure material and communication skills at the same time. Media are materials and tools used to help the process of delivering information. One of the media that can be an alternative to overcome existing chemical problems is the spinning wheel-based question thread pull media, which is a media in the form of practice questions, and the answers must be communicated directly. The purpose of this study was to determine the validity of spinning wheel-based question thread pull media as a learning media to train communication skills on atomic structure material. This type of research is Research and Development (R&D) with the 4D (four-D) model, namely define, design, develop, and disseminate. However, this research is limited to the development stage only, which focuses on media validation. The research instrument used was a validation sheet given to three validators, namely two lecturers from the Chemistry Education Study Program and one chemistry teacher. The data analysis technique used is the mode. The results showed that the content validity and construct validity of the spinning wheel-based question thread pull media in each aspect of the assessment were ≥ 3, with a good category. So it can be concluded that the spinning wheel-based question thread pull media developed is declared valid as a learning media in schools to train the communication skills of class X senior high schools or Islamic high school students on atomic structure material. For further research, it is recommended that the media carry out a limited trial as well, so that its practicality and effectiveness can be known.